Isolasi dan Identifikasi Jamur Xerofilik pada Kopi Instant - Kartinah Wiryosoendjojo; Nony Puspawati; Dewi Sulistyawati (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
The process of producing instant products (including instant coffee) if not properly maintained, can cause microbial contamination which is harmful to health. Microbial contamination can cause diarrhea, poisoning and even death. Some xerophilic molds can produce mycotoxins which can cause poisoning. In this research, it will be investigated whether instant coffee which is marketed in Sleman, Yogyakarta contains xerophilic molds and what are the types. This research is an observational research. Sampling is done randomly. Instant coffee samples taken in the area of ​​Sleman, Yogyakarta consists of 5 instant coffee of various brands. The inoculation was carried out with a sprinkling technique on DG 18 media (Dichloran 18% Glycerol). The results of this study prove that instant coffee in Sleman, Yogyakarta contains xerophilic mushroom spores. The types of xerophilic molds found in instant coffee in Sleman, Yogyakarta are Fusarium culmorum, Aspergillus niger, Curvularia lunata, Cladosporium macrocarpum, Geotrichum candidum.